Multi-method research strategy for understanding changes in barley grain protein composition and its relation to improved nutritional quality - Schmidt, Daiana (2015)
Barley (Hordeum vulgare L.) is the fourth largest produced cereal worldwide. About two thirds of barley production is used to animal feed. When used to feed monogastric animals, the main shortcoming of barley grains is the deficiency of essential amino acids, especially lysine, threonine and methionine. The unbalanced amino acid composition is due to the main storage protein, the hordeins, which account for about 50% of total grain protein content. The nitrogen fertilization promotes C-hordein expression and accumulation, the hordein subgroup with the lowest content of essential amino acids, and the highest content of non-essential amino acids. Due to the importance of grain protein content and composition in the end use grain quality the key objective of the present study was to obtain a detailed insight into synthesis and accumulation of barley grain proteins and their relation to improved nutritional quality. An integrated proteomic and transcriptomic analysis have been undertaken in a set of transgenic antisense barley lines with the grain protein profile altered in comparison to the non-transgenic line cv. Golden Promise. The results were presented in three manuscripts in the thesis (chapters 2, 3 and 4). The first manuscript (chapter 2) reported a new grain protein extraction method combined with multi-method protein evaluation, including biochemical quantification, amino acid composition, sodium dodecyl-polyacrylamide gel electrophoresis (SDS-PAGE) couple with mass spectrometry (MS) identification and a gel free shotgun MS identification and relative quantification. The results showed the changeability of proteins between protein groups and the importance of choosing an adequate proteomic-based method for protein identification according to the complexity of protein mixtures. In the second manuscript (chapter 3) a differential protein profile of non-transgenic barley cv. Golden Promise and the transgenic antisense C-hordein barley lines was achieved by two-dimensional gel electrophoresis (2-DE) for salt soluble proteins and the differentially expressed proteins were identified by MS. The key results showed that the suppression of C-hordeins, the poor nutritional hordein subgroup, does not exclusively affects hordein synthesis and accumulation, and that the more balanced amino acid composition of these lines may be a consequence of distinct protein sources among different transgenic events, though a stable lysine-rich proteins upregulation occurs in all lines. In the third manuscript (chapter 4) the effects of nitrogen fertilization on hordein family at transcriptional and proteome level were assessed. The main results showed differential responses to N nutrition between non-transgenic and transgenic lines. In relation to C-hordein, specific C-hordein downregulation effect and in particular different responses to N were verified among subgroups of C-hordein multigene family in the transgenic line at transcriptional and proteomic level. In summary, the multi-method strategy used in the present work was successfully applied to obtain comprehensive information about barley grain proteins synthesis and accumulation and explain, at least in part, their relation to improved nutritional quality. These results can be useful in barley breeding programs aiming selective alterations of specific alleles/homologues to change amino acid composition by changing the relative proportions of the grain proteins in order to improve the barley grains nutritional quality.